2010
DOI: 10.1097/anc.0b013e3181ef7de2
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation and Heat Loss Prevention After Birth and During Neonatal Intensive-Care Unit Stabilization of Extremely Low-Birthweight Infants

Abstract: Extremely low-birthweight infants have inefficient thermoregulation due to immaturity and may exhibit cold body temperatures after birth and during their first 12 hours of life. Hypothermia in these infants can lead to increased morbidity and mortality. Anecdotal notes made during our recent study revealed extremely low-birthweight infants' temperatures decreased with caregiver procedures such as umbilical line insertion, intubations, obtaining chest x-rays, manipulating intravenous lines, repositioning, sucti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…In Veneto, during the eighteenth and nineteenth centuries, several issues may have augmented these risks. More specifically, it should be underlined that low-weight newborns are less able to react and adapt to the temperature shock which typically characterizes the hours following delivery, especially when external temperatures are low (see WHO 1997;Costello 2000;Kambarami and Chidede 2003;Darmstadt et al 2006;Knobel and Holditch-Davis 2007). Evidence of general malnourishment suggests that underfed mothers may have given birth to low-weight infants.…”
Section: Causes Of Deathmentioning
confidence: 96%
“…In Veneto, during the eighteenth and nineteenth centuries, several issues may have augmented these risks. More specifically, it should be underlined that low-weight newborns are less able to react and adapt to the temperature shock which typically characterizes the hours following delivery, especially when external temperatures are low (see WHO 1997;Costello 2000;Kambarami and Chidede 2003;Darmstadt et al 2006;Knobel and Holditch-Davis 2007). Evidence of general malnourishment suggests that underfed mothers may have given birth to low-weight infants.…”
Section: Causes Of Deathmentioning
confidence: 96%
“…Extremely low birth weight infants have higher body temperature on admission to the NICU if they are immediately put into polyethylene bags before drying [32,33]. Vohra et al [32] reported that wrapped infants <28 weeks of gestational age had a significantly higher mean rectal admission temperature of 36.5°C (SD 0.8) compared to 35.6°C (SD 1.3) in control infants.…”
Section: Thermal Controlmentioning
confidence: 99%
“…At 1 h later, the mean rectal temperatures were similar in both groups (36.6°C, SD 0.7 vs. 36.4°C, SD 0.9). Size at birth was an important determinant of heat loss - mean rectal admission temperature increased by 0.21°C (95% CI 0.04-0.40) with each 100-gram increase in birth weight [33]. It is important to remember that in infants in need of ventilatory support heated humidified inspiratory gas at delivery until the arrival of the neonatal unit improves admission temperature [34].…”
Section: Thermal Controlmentioning
confidence: 99%
“…15Á18; for Veneto 1675Á1775: Rosina and Zannini 2004, p. 36;for Veneto 1800Á1900: Del Panta 1997. Data are interpolated with third-or fourth-order polynomials) 234 Renzo Derosas the medical literature they cite on the relationship between low birth weight, cold temperatures, and neonatal mortality refers explicitly to hypothermia (Jeghers 1976;WHO 1997;Costello 2000;Kambarami and Chidede 2003;Knobel and Holditch-Davis 2007). Indeed, once respiratory diseases are excluded, there is little besides hypothermia that could have caused deaths related to exposure to the cold.…”
mentioning
confidence: 98%